Spectrum of Cardiovascular Diseases in the Cardiology Unit of Bharatpur Hospital - Gautam, Mani Prasad; Bhattarai, Surakshya; Kandel, Sanjog; Panjiyar, Rajesh; Shrestha, Bishal (Journal of National Heart and Lung Society Nepal, 2024)
Background: Cardiovascular diseases (CVDs) are a leading cause of morbidity and mortality worldwide and its burden is on rise. CVDs encompass a range of disorders, including ischemic heart disease, valvular heart diseases, heart failure, arrhythmias, and hypertensive heart disease. Understanding the patterns of CVDs in our setting, where advanced interventional care is unavailable, can inform strategies for improving patient care, optimizing resources, and guiding healthcare policy. The study aimed to evaluate the spectrum of cardiovascular diseases (CVDs) in the cardiology unit of Bharatpur Hospital. Methods: A retrospective observational study was designed and conducted at the cardiology unit of Bharatpur Hospital from September 1, 2023, to August 31, 2024. A total of 294 subjects were included in the study. Data were collected from hospital records and cardiovascular conditions were categorized into major groups: heart failure, ischemic heart disease, valvular heart diseases, arrhythmias, hypertensive heart disease. Descriptive statistics were used to analyze the data, with continuous variables summarized as means and standard deviations, and categorical variables presented as frequencies and percentages.. Results: Mean ±SD of age was 65.2± 12.8 years. Hypertension (40.14%), diabetes mellitus (29.93%), and smoking (25.17%) were the common comorbidities. Among cardiovascular conditions, heart failure was the commonest (46.60% ) followed by ischemic heart Disease (18.03%), valvular heart disease ((16.33%) and hypertensive heart disease: (6.46% ). Arrhythmias was noted in 6.12% with paroxysmal supraventricular tachycardia as the commonest one. In-hospital mortality was 6.12%, highest in those with decompensated heart failure and advanced valvular heart disease. Conclusion: The study highlights the significant burden of heart failure, ischemic heart disease and valvular heart disease in cardiology unit. Other less common conditions included hypertensive heart disease and arrhythmias. The study emphasizes the need for improving cardiovascular disease management, advocating for the establishment of advanced interventional cardiology facilitiesand better management strategies for chronic risk factors.